BARRIERS TO CIVIL RIGHTS: ANALYZING THE RACIAL DISCRIMINATION PORTRAYED IN AVA DUVERNAY’S SELMA - Hardian, Gilang (Pengkajian Amerika, Universitas Gadjah Mada, 2025)
In this article, the author wants to examine the racial discrimination experienced by Black people in the Selma movie and analyze the struggles of Martin Luther King Jr. against the inequality of African American rights. In this research, the author used a qualitative method through library research. The Selma movie's pictures and conversation are used as the study’s primary source of data for analysis, and this research also relies on secondary data by examining academic articles, books, internet sources, and other readings related to the research topic. The author applied a post-nationalist perspective, Talcott Parsons' structure of functionalism and race discrimination theory. The result of this research is that four types of racial discrimination were identified: direct discrimination, indirect discrimination, harassment, and victimization, all perpetrated by the white race against the black race. Furthermore, Martin Luther King Jr.’s struggle can be understood through Parsons’s four structures of functionalism: adaptation, goal attainment, integration, and latent pattern maintenance.